Understanding Nitrogen Availability from Applications of Anaerobically Digested Beef-Cattle Manure in Florida Sandy Soil - Rishi Prasad; George Hochmuth (EDIS)
Anaerobic digestion of livestock manure is a microbe-mediated process carried out in vessels or tanks, where the livestock wastes are digested slowly in environment absent of oxygen. The main products are biogas, anaerobically digested liquid (ADL), and solid (ADS), which can be land-applied as an organic soil amendment or a source of plant nutrients. This 4-page fact sheet provides research-based information about using anaerobically digested beef-cattle manure as an organic source of nitrogen for supplementing crop nutrition in Florida sandy soils, including initial N concentration, application timing, rate of application, and method of application. Written by Rishi Prasad and George Hochmuth, and published by the UF Department of Soil and Water Science, April 2015. (Photo: George Hochmuth, UF/IFAS)